Предмет: Математика,
автор: anadomovaa77
2 – 3х > 3х + 1
3 – х ≤ 4 + 6х
Ответы
Автор ответа:
0
ОТВЕТ
1.
2.
Пошаговое объяснение:
1.
2.
Автор ответа:
0
1) 2 - 3x > 3x + 1
3x + 3x < 2 - 1
6x < 1
x < 1/6
2) 3 - x <= 4 + 6x
6x + x => 3 - 4
7x => - 1
x => - 1/7
Ответ: 1) (- бесконечности; 1/6); 2) [- 1/7; + бесконечности).
3x + 3x < 2 - 1
6x < 1
x < 1/6
2) 3 - x <= 4 + 6x
6x + x => 3 - 4
7x => - 1
x => - 1/7
Ответ: 1) (- бесконечности; 1/6); 2) [- 1/7; + бесконечности).
Похожие вопросы
Предмет: Қазақ тiлi,
автор: saleiko
Предмет: Русский язык,
автор: Аноним
Предмет: Английский язык,
автор: VladaKorablina
Предмет: Химия,
автор: tyrell